Implementing CRISPR-Cas technologies in conventional and non-conventional yeasts: Current state and future prospects - Raschmanová, Hana; Weninger, Astrid; Glieder, Anton; Kovar, Karin; Vogl, Thomas (Biotechnology advances, 2018)
Within five years, the CRISPR-Cas system has emerged as the dominating tool for genome engineering, while also changing the speed and efficiency of metabolic engineering in conventional (Saccharomyces cerevisiae and Schizosaccharomyces pombe) and non-conventional (Yarrowia lipolytica, Pichia pastoris syn. Komagataella phaffii, Kluyveromyces lactis, Candida albicans and C. glabrata) yeasts. Especially in S. cerevisiae, an extensive toolbox of advanced CRISPR-related applications has been established, including crisprTFs and gene drives. The comparison of innovative CRISPR-Cas expression strategies in yeasts presented here may also serve as guideline to implement and refine CRISPR-Cas systems for highly efficient genome editing in other eukaryotic organisms.
Keywords: Synthetic biology; Chromosomes, Fungal; Expression optimization; klonování DNA; Saccharomyces cerevisiae; Candida albicans/glabrata; Microorganisms, Genetically-Modified; CRISPR-Cas systémy; CRISPR-Cas Systems; Schizosaccharomyces pombe; Yarrowia; vodící RNA, systémy CRISPR-Cas; Metabolic engineering; metabolické inženýrství; CRISPR-Cas; Yarrowia lipolytica; Cloning, Molecular; Gene Drive Technology; Gene Editing; regulace genové exprese u hub; Pichia; Yeasts; Metabolic Engineering; kvasinky; Point Mutation; bodová mutace; chromozomy hub; Gene Expression Regulation, Fungal; geneticky modifikované mikroorganismy; technologie gene drive; Pichia pastoris; editace genu; RNA, Guide, CRISPR-Cas Systems